Correlation between cortico-hypothalamic-pituitary system with the female genital tract. - Schiavo, Carlos (2015)
Advances in electron microscopy that allowed unravel the cellular ultrastructure, and biochemistry of hormone we clarified the molecular composition of hormones, are those that have allowed us to get to know the correlation between the cortico-hypothalamic-pituitary system and the female genital tract.